Local Stakeholders' Perception Survey - Gilani, Ijaz; Mir, Aized H.; Malik, Ermeena (World Bank, Washington, DC, 2014)
This paper identifies issues in implementing large infrastructure projects in Pakistan. Input from key stakeholders of the construction industry (consultants, clients, and contractors) was required to gauge their perceptions about the existing problems in the industry and their suggested solutions. This was necessary to compare what the stakeholders considered were hurdles in their growth with what this study identified as the main problems within the construction industry. Therefore, perceptions of stakeholders were deemed essential to identify priority issues within the construction industry so that solutions to improve the implementation capacity of the industry are directed towards these areas. While the overall perception among contractors and consultants was one of disillusionment with clients and government procedures, they were modestly upbeat about future business prospects. They recognized that economic activity was rising in Pakistan and that there were prospects for them both there and abroad. They referred to the period since the 1990s as a period of lost opportunity, during which they faced a serious slump, but were now modestly hopeful and keen on moving ahead. While they put some of the blame on the clients, they were generally pragmatic and mindful of their own shortcomings. The survey findings and deliberations in the focus group discussions showed a similarity of views on key issues pertaining to the four thematic areas, namely, business environment, human resources, supply of materials, and equipment. Conclusions are drawn that contract provisions for timely payments to sub-contractors need to be strengthened.